OPTIMALISASI FUNGSI BREAKWATER PELABUHAN PENDARATAN IKAN (PPI) TANAH BERU KABUPATEN BULUKUMBA - Purwasih, Ratih; Rahman, Sabaruddin; Umar, Hasdinar (Riset Sains dan Teknologi Kelautan, 2024)
At the Fish Landing Harbor (PPI) coastal protection buildings have been built to protect the area in an effort to obtain calm waters at the harbor. A breakwater is infrastructure built to break waves by absorbing wave energy. The types of wave breakers are sloping side breakwaters, vertical side breakwaters and mixed wave breakers. Waves are a form of energy that can shape beaches, cause currents and sediment transport in perpendicular directions and along the coast, and cause forces that act on coastal buildings. The aim of this research is to determine the characteristics of wave transmission and alternative breakwater construction in ports, simulated using a numerical hydrodynamic model to simulate waves. The input data is wave height, wave period and wave direction. The Fish Landing Harbor Breakwater (PPI) is not yet optimal because the waves entering the port area in the west season reach 1.2 meters. Based on the results of the breakwater design used to optimize its function, this can be proven by the existence of breakwater construction designed in modeling where the breakwater with a length of 150 m, the wave height entering the protected area is 0.81 m, the breakwater with a length of 300, the wave height entering the area protected by 0.2 m, and a breakwater with a length of 500, the wave height entering the protected area is 0.03 m.